Effectiveness of cold-water immersion vs. massage in reducing delayed-onset muscle soreness and enhancing recovery following CrossFit® Murph Workout: Randomized rial - Gabrielly Santos Pereira; Giovana Eduarda Paulino; Thais Helena Martins Faria de Almeida; Cissa Maria Ribeiro Siqueira; Josie Resende Torres da Silva; Marcelo Lourenço da Silva; Luciano Maia Alves Ferrera (PLoS ONE, 2025)
The Murph workout, one of the most challenging CrossFit® workouts, demands endurance and high intensity. This WOD (Workout of the Day) includes a 1-mile run, 100 pull-ups, 200 push-ups, 300 air squats, and another 1-mile run, typically performed while wearing a weighted vest. Due to its high physical demands, athletes commonly experience Delayed Onset Muscle Soreness (DOMS), characterized by increased sensitivity, fatigue, and reduced muscle function. To minimize these effects and ensure proper recovery, it is essential to adopt strategies that restore muscle function, reduce pain, and allow athletes to return to training without an elevated risk of injury. Thus, the objective of this study was to investigate the effects of massage therapy (MAS) or cold-water immersion (CWI) as a recovery intervention for DOMS in athletes following high-intensity physical activity during the CrossFit® Murph workout. For this purpose, thirty individuals with a minimum of six months of CrossFit® experience and familiarity with all exercises used in the study were recruited. Pain assessment questionnaires, including the Brief Pain Inventory (BPI) and the A-DOM questionnaire, along with a socioeconomic questionnaire, were administered before and after WOD. Additionally, pain assessments were conducted using algometry and thermographic imaging. After completing the WOD, participants were randomly assigned to one of two recovery interventions: MAS or CWI. The study results highlight the differential impacts of CWI and MAS on pain management and recovery dynamics following structured exercise. Our findings clearly demonstrate that CWI significantly reduces pain prevalence, both at rest and during exercise, as evidenced by the absence of pain reports from participants 48 hours after the intervention. While our study provides valuable insights into the effectiveness of CWI and MAS for post-exercise recovery, limitations such as the non-blinded study design and small sample size may influence the generalizability of the findings.